Maṭbūʻāt al-ʻUmānīyīn fī Miṣr wa-Dawruhā fī Nashr al-Waʻy bi-al-Turāth al-ʻUmānī: Dirāsah ḥawla Maṣādir al-Tārīkh al-ʻUmānī al-Manshūrah fī Miṣr - Zaydān, Aḥmad Saʻīd al-Sayyid (al-Muʼtamar al-Duwalī al-Khāmis bi-Mālīziyā: Ḥarakat al-Ṭibāʻah al-ʻUmānīyah wa-Atharuhā fī al-Tawāṣul al-Ḥaḍārī, 2018)
The Omani heritage is rich and varied: the Sultanate of Oman has a history reaching back more than three thousand years before the Common Era, and a clear influence on the movement of history across the Indian Ocean, the Arabian Gulf, East Africa and the Arabian Peninsula. Certain Omani works are filled with numerous and important events in Omani history and are a principal source for reading that history. The spread of printing in Egypt had its effect in leading some Omanis to print their works there, and from this the idea of the study arose, concerned principally with historical publications. The Egyptian National Library holds many such studies, among them Omani genealogical books, biographies and lives of Omanis, Omani annalistic history and many other important writings, upon which this study sheds light.
MHF-PRINT2018-029
Keywords: Omani publications; Egypt; Omani history; Egyptian National Library; Printing history; Historical sources